A Textbook Evaluation of Socio-Cultural Contexts in “Got It Series” - Mehdi Nasri; Ehsan Namaziandost; Elnaz Zariholhosseini (Sekolah Tinggi Agama Islam Negeri Majene, 2022)
This study investigated the appropriateness of socio-cultural contexts in Got It Series. To do so, a survey questionnaire was applied to elicit the teachers and supervisors’ perceptions towards the Series. The findings revealed that the intercultural content of the Series was understandable and positively evaluated by the participants. However, according to the results of this test, there were significant differences among the means of these categories. The results suggested that among five categories in the questionnaire, the highest mean belonged to cultural presentation. In addition, the lowest mean belonged to aims and achievements. Variance analyzed accompanying with repeated measure ANOVA were used to compare the means. According to the results of this test, there were significant differences among the means of these categories. The results of Bonferroni Post-Hoc suggested that the mean of the aims and achievements was less in comparison to other categories, and there were no significant differences among other categories. The supervisors agreed more with the questions included in category D in comparison to the teachers. Moreover, there were no significant differences between these two groups in other categories.